Nasal mucosa and blood cell transcriptome profiles do not reflect respiratory symptoms associated with moisture damage. (6th June 2018) - Ndika, J.; Suojalehto, H.; Täubel, M.; Lehto, M.; Karvala, K.; Pallasaho, P.; Sund, J.; Auvinen, P.; Järvi, K.; Pekkanen, J.; Kinaret, P.; Greco, D.; et al.
Abstract: Upper and lower respiratory symptoms and asthma are adverse health effects associated with moisture‐damaged buildings. Quantitative measures to detect adverse health effects related to exposure to dampness and mold are needed. Here, we investigate differences in gene expression between occupants of moisture‐damaged and reference buildings. Moisture‐damaged (N = 11) and control (N = 5) buildings were evaluated for dampness and mold by trained inspectors. The transcriptomics cohort consisted of nasal brushings and peripheral blood mononuclear cells (PBMCs) from 86 teachers, with/without self‐perceived respiratory symptoms. Subject categories comprised reference (R) and damaged (D) buildings with (S) or without (NS) symptoms, that is, R‐S, R‐NS, DS, and D‐NS. Component analyses and k‐means clustering of transcriptome profiles did not distinguish building status (R/D) or presence of respiratory symptoms (S/NS). Only one nasal mucosa gene ( YBX3P1 ) exhibited a significant change in expression between D‐S and D‐NS. Nine other nasal mucosa genes were differentially expressed between R‐S and D‐S teachers. No differentially expressed genes were identified in PBMCs. We conclude that the observed mRNA differences provide very weak biological evidence for adverse health effects associated with subject occupancy of the specified moisture‐damaged buildings. This emphasizes the need to evaluate all potential factors (including those not related to toxicity) influencing perceived/self‐reported ill health in moisture‐damaged buildings.